(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
The ability of the braking system in motorized vehicles is important because it affects driving safety. Brake lining is a very important component in the vehicle braking system, related to safety factors in driving. The level of wear and tear on the brake pads and the age of use must be considered, as well as the brand and quality when selecting the type of brake lining that will be used for the long term in the future. Everything that is rushed will definitely decrease with use. This research was conducted to test the comparison of brake linings which aims to find the value of the wear rate and also the service life according to the rear brake linings used, namely Pacific and KMJG brands. This research was conducted at the Laboratory of the University of Balikpapan. The purpose of this study was to test the braking performance of Pacific and KMJG brake pads at speeds of 20, 30 and 40 kilometers per hour. Testing of electric motorcycles with a hand-held pallet on the rear wheel braking system was carried out at a predetermined speed in standby or stand still to see how effectively the brake pedal can stop the bike. The brake pads in the Pacific sample have a wear rate of 0.5286 gr/mm2.sec. This is lower than the liner wear rate in the European sample, which is 0.6875 gr/mm2.sec. The brake pads with the highest wear value are KMJG brake pads with a value of 2.1418 gr/mm2.second.